2004
DOI: 10.1111/j.1551-2916.2004.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized Densification during the Stage II–III Transition ‐ Compaction Efficiency at High Pressures

Abstract: Localized densification and compaction efficiency at high pressures was studied using X‐ray computed tomography. Stage III begins with the initiation of a region of uniform average density within the overall high‐density zone. No further densification occurs in this region; additional pressure is transmitted into adjacent, less‐dense zones and the die wall. This localized increase in wall friction continuously decreases compaction efficiency. Discrete element modeling was used to visualize force transfer. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(30 reference statements)
1
7
1
Order By: Relevance
“…The stress-density relationship provides no evidence of localization within the compacting sample. However, previous ceramic compaction experiments and modeling (Kong and Lannutti, 2000;Nam and Lannutti, 2004) have shown that non-uniform densities can develop in the specimen, albeit at lower stresses than in the current experiments.…”
Section: Static Compaction Of Tungsten Carbide Powdercontrasting
confidence: 65%
“…The stress-density relationship provides no evidence of localization within the compacting sample. However, previous ceramic compaction experiments and modeling (Kong and Lannutti, 2000;Nam and Lannutti, 2004) have shown that non-uniform densities can develop in the specimen, albeit at lower stresses than in the current experiments.…”
Section: Static Compaction Of Tungsten Carbide Powdercontrasting
confidence: 65%
“…Thus, DEM offers a unique tool to introduce pertinent microstructural characteristics into simulations. It is worth noting that the DEM generated compaction curves clearly reproduce the three stages of compaction that are generally observed in aggregated powders 14 . This has been obtained naturally by introducing simple contact laws together with realistic material parameters in the simulations.…”
Section: Discussionsupporting
confidence: 52%
“…As observed experimentally for many types of aggregated powders, 13,14,32–34 no significant densification takes place in the first part until a certain critical axial stress, σ c , is reached. Comparison of Figs.…”
Section: Packings Of Aggregatesmentioning
confidence: 54%
See 2 more Smart Citations